Hybrid Polymer Gear Concepts to Improve Thermal Behavior - Carlos M C G Fernandes (2019)
A drawback of polymer materials is their low thermal conductivity which affects the operating temperature of polymer gears. The mechanical properties of a polymer gear are critically dependent on the maximum operating temperature. In order to improve thermal behavior of polymer gears, a hybrid polymer gear concept is suggested which consists of a polymer gear tooth with a metallic insert to promote heat evacuation from the meshing surface. The material selection based on finite element method (FEM) simulations showed that an aluminum insert performed better than copper and steel for a hybrid polymer gear. The results show that an aluminum insert increases the mass by 9% in comparison with a standard polymer gear but it decreases the maximum operating temperature by 28%. Insert geometries of different complexity were studied and their influence on operating temperature assessed.